(untitled) (Journal of Economic Research & Business Administration, 2015)
Tax deductions are an important instrument in the tax adjusting and administration. Tax deductions are called to carry out a stimulant and social function. In the economy of country by means of tax deductions affect activity of managing subjects, creating favourable business climate. Tax deductions create certain advantages and for the separate categories of population, businessmen. Tax deductions create certain advantages and for the separate categories of population, businessmen. Tax deductions corresponding to the certain tax have certain lines, signs and forms, distinguishing them from other instruments of the tax adjusting. On the basis of these approaches it is possible to classify the tax deductions applied in Kazakhstan on the basis of current tax legislation.